Manajemen Sarana dan Prasarana dalam Meningkatkan Mutu Pendidikan di Sekolah - Delfi Nome; Gracia Yuardila Selan; Stiven Manu; Rivan Robinson Taneo; Sandy Onaldi Selan; Yanti Y. E. Sole (Indo Publishing, 2026)
Management of facilities and infrastructure is an important factor in improving the quality of education in schools. Good management of facilities and infrastructure can support the learning process so that it runs effectively, efficiently and comfortably for students and teaching staff. This research aims to find out how management of facilities and infrastructure can improve the quality of education in schools. The method used is a qualitative approach with data collection techniques through observation, interviews and documentation. The research results show that planning, procurement, maintenance and supervision of facilities and infrastructure carried out regularly can improve the quality of the teaching and learning process. Apart from that, the availability of adequate facilities also influences student learning motivation and teacher performance. Thus, effective management of facilities and infrastructure is one of the strategic efforts to improve the quality of education in schools.